Measurement of acetabular inclination and anteversion via CT generated 3D pelvic model - R. Y. Wang; W. H. Xu; X. C. Kong; L. Yang; S. H. Yang (BMC Musculoskeletal Disorders, 2017)
Abstract Background Inclination and anteversion were the main factors that determined the reliability of the acetabulum. Inclination and anteversion measurements included anatomical, operational and radiographic methods. The aim of our present study was to exhibit divergence of inclination and anteversion via the three measurements. Methods Inclination and anteversion were defined according to the definitions put forward by Murray. Three-dimensional models of pelvis of CT data were brought forth. Acetabular axis was determined by the rim of acetabula. Reference planes were established by bone landmarks including anterior superior iliac spine, pubic tubercles and sacral crests. Inclinations and anteversions were calculated according to the definitions. Results Forty-nine cases were involved in the research. Data of inclination form anatomical, operational and radiographic showed 37.48 ± 11.07, 45.12 ± 14.76 and 48.76 ± 14.36, and anteversion were 18.12 ± 7.59, 24.97 ± 9.68, 14.30 ± 5.64. A substantial deviation was noted in the inclinations (P < 0.01) and anteversions (P < 0.01). Conclusion Our findings suggested that the inclinations and anteversions of the three measurements varied, which might in turn interfere the decision of orthopedists.